Microplastic pollution in vulnerable karst environments: case study from the Slovenian classical karst region - Valentić, Lara; Kozel, Peter; Pipan, Tanja (Acta Carsologica, 2022)
Since the start of mass production of plastic materials more than a century ago, the problem of accumulating plastic waste in the environment has reached epic proportions. Recently, the problem of smaller plastic particles (microplastic, MP) in the environment has become a widely studied topic, but the amount and types of MP in karst environments are still poorly known. Thus, the objective of this study was to collect and analyse samples from various karst habitats and to try and determine the scope of pollution in karst springs that are in part used as sources for drinking water. Of the potential pollution sources, we sampled rainwater, two discharges from wastewater treatment plants, and a leachate from a landfill. We conducted polymer analyses of potential MP particles using FTIR-ATR. The results showed that eight samples from the Postojna region (Postojna–Planina Cave System, rainfall sample and surface streams) contain up to 444 MP particles per m3. However, 32 samples taken from the Škocjan–Kačna–Jama 1 v Kanjaducah Cave System contain up to 60,000 MP particles per m3, with the bulk of particles found in the sediment samples from Škocjan Caves – Kačna Cave System. Samples from Postojna region contained mostly PET, PU and PA polymers, with a minor inclusion of polymers of plastic sponge used for cleaning. Samples from Škocjan region contained mostly PP, PET and PE polymers, with some of PA and PU polymers. Sediment samples contained much less MP particles compared to water samples, which indicates fast transport through karst aquifer.